Functional and aesthetic compatibility between advertising billboards and interior design - Doaa Ahmed Mohamed Mantawi; Wessam Ezzeldin (Journal of Architecture, Art & Humanistic Science, 2022)
The research examines the functional and aesthetic compatibility between billboards and interior design and the ability of interior design to employ billboards and use them as a formative element within the inner space; The designer faces many challenges due to the random spread of billboards within the space such as centers and shops, distorting the beauty of the interior and architectural design of the place. Where the trend now in Egypt is to preserve the architectural and cultural identity, this research came to contribute to the creation of the aesthetic image in accordance with the functional and design values of the place, which require the development of appropriate solutions to provide psychological and functional comfort to the human and reduce that random spread of billboards; Although these billboards may be good in terms of design, their spread in an unconsidered and orderly manner feels uncomfortable, One of the most important functions of the interior designer is to optimize the interior spaces, where he develops a preliminary conception of the design functionally and aesthetically and create a well-thought-out and structured creative idea of the venues of these billboards within the interior design and employ them in a way that attracts the attention of customers and attracts them to the place.The distribution of billboards within the interior should be based on specific requirements for the translation of the required visual and cognitive message and the nature of the visual communication of the individual within the place in which he displays, and must be organized colors, lines, spaces and sizes within visual and temporal hierarchies that preserve the values of harmony and beauty between them, and at the same time are consistent with the functional pattern and determinants of human activity within the void, As well as developing some solutions and design considerations that contribute to the appropriate distribution and technical treatment of those different advertising spaces within the space, and consider it as one of the elements of the interior design of the place, and thus adjust the goal of the nature of the cognitive structure to be reached in the receiving human